Progress of Individualized Chemotherapy for Gastric Carcinoma Under the Guidance of Genetic Testing - Jin, Xin; Jiang, Meng-lin; Wu, Zhao-Hui; Fan, Yu (Current Medicinal Chemistry, 2020)
Background: Gastric cancer is a major malignancy that has high incidence rates worldwide. Approximately 30% of patients with gastric cancer have progressed into advanced stages at the time of diagnosis. Chemotherapy is the standard-of-care for most advanced gastric cancer and elicits variable responses among patients. Personalized chemotherapy based on genetic information of individual patients with gastric cancer has gained increasing attention among oncologists for guiding chemotherapeutic regimens. Methods: This review summarizes recent progress of individualized chemotherapy in gastric cancer guided by pharmacogenomics. Variable medical research search engines, such as PubMed, Google Scholar, SpringerLink and ScienceDirect, were used to retrieve related literature. Only peerreviewed journal articles were selected for further analyses. Results and Conclusion: The efficiency of chemotherapy in patients with gastric cancer is not only determined by chemotherapeutic drugs but is also directly and indirectly influenced by functionally correlative genes. Individual gene alteration or polymorphism remarkably affects patients’ responses to particular chemotherapy. Most studies have focused on the influence of single-gene alteration on a selected drug, and only a few works explored the interaction between therapeutics and a panel of genes. Individualized chemotherapy regimens guided by a genetic survey of a multiple-gene panel are expected to remarkably improve the treatment efficacy in patients with advanced gastric cancer and may become the new standard for personalizing chemotherapy for gastric cancer in the near future.
Keywords: drug resistance